2020
DOI: 10.1002/chem.201905466
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐Mediated Catalytic Hydrogenation of Monocyclic and Polycyclic Arenes

Abstract: Two electron‐reduction of the TiIV guanidinate complex (ImDippN)(Xyketguan)TiCl2 gives (η6‐ImDippN)(xyketguan)Ti (1intra) and (ImDippN)(Xyketguan)Ti(η6‐C6H6) (1inter) (Xyketguan=[(tBuC=N)C(NXylyl)2]−, Xylyl=2,5‐dimethylphenyl) in the absence or presence of benzene, respectively. These complexes have been found to hydrogenate monocyclic and polycyclic arenes under relatively mild conditions (150 psi, 80 °C)—the first example of catalytic, homogeneous arene hydrogenation with TON >1 by a Group IV system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…The Ti–Ti distances (avg., 3.07 Å) in 2 are significantly elongated than in 1 ·1.5C 7 H 8 , while exhibiting inequivalent Ti–N Im bridging distances with average lengths of 1.98 and 2.17 Å. Subtle structural changes between the two polymorphs do exist, namely the titanium bonded η 6 -aryl ring in 2 - Pccn exhibits a boat conformation where the ipso and para carbon atoms deviate from the ring plane by 11° and 5°, respectively, whereas the masking aryl substituent in 2 - P 1̅ adopts a puckered ring, similar to that found in A and B , with an average fold angle of 12.6°, slightly larger than the 10° of A . However, the ring fold in 2 - P 1̅ falls along an ortho / meta carbon atom vector, unique from the ipso / para carbon atom fold planes of A and B .…”
Section: Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The Ti–Ti distances (avg., 3.07 Å) in 2 are significantly elongated than in 1 ·1.5C 7 H 8 , while exhibiting inequivalent Ti–N Im bridging distances with average lengths of 1.98 and 2.17 Å. Subtle structural changes between the two polymorphs do exist, namely the titanium bonded η 6 -aryl ring in 2 - Pccn exhibits a boat conformation where the ipso and para carbon atoms deviate from the ring plane by 11° and 5°, respectively, whereas the masking aryl substituent in 2 - P 1̅ adopts a puckered ring, similar to that found in A and B , with an average fold angle of 12.6°, slightly larger than the 10° of A . However, the ring fold in 2 - P 1̅ falls along an ortho / meta carbon atom vector, unique from the ipso / para carbon atom fold planes of A and B .…”
Section: Results and Discussionmentioning
confidence: 87%
“…In recent years, impressive strides have been made in the development of the low-valent chemistry of the early metals (electron counts ≥ d 2 ), showing these systems to be formidable reductants capable of small molecule activation that can also mediate important organic chemistries. In our own laboratory, we have shown that the reduced arene-masked titanium complexes ( Arket guan)­Ti­(η 6 -NIm Dipp ) ( Arket guan = [( t Bu 2 CN)­C­(NAr) 2 ] − , Ar = C 6 H 3 -2,6- i Pr 2 ( A ), C 6 H 3 -3,5-Me 2 ( B ); Im Dipp N = [1,3-bis­(Dipp)­imidazolin-2-iminato] − , Dipp = C 6 H 3 -2,6- i Pr 2 ) (Chart ) can perform the catalytic hydrogenation of mono- and polycyclic aromatic hydrocarbons as well as accomplish the hydrodesulfurization (HDS) of thiophene. The latter example is particularly noteworthy, as the titanium complex shows a very rare display of fully reversible, early metal oxidative-addition/reductive-elimination during the initial HDS step involving ring opening of the thiophene. Nevertheless, these chemistries are limited to two-electron redox cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Rothwell has demonstrated the activity of alkoxide-supported tantalum and niobium , alkoxide complexes in racemic hydrogenations. More recently, Fortier has reported homogeneous titanium complexes that catalyze the hydrogenation of benzene and naphthalene derivatives . Diastereoselective xylene hydrogenation has been described by Marks and co-workers using supported zirconocene complexes, demonstrating that a combination of molecular and heterogeneous catalysis is beneficial for catalyst activity and selectivity. …”
Section: Introductionmentioning
confidence: 99%
“…More recently, Fortier has reported homogeneous titanium complexes that catalyze the hydrogenation of benzene and naphthalene derivatives. 29 Diastereoselective xylene hydrogenation has been described by Marks and co-workers using supported zirconocene complexes, demonstrating that a combination of molecular and heterogeneous catalysis is beneficial for catalyst activity and selectivity. 30−32 By comparison to their monocyclic counterparts, fused arenes and heteroarenes are less-challenging substrates for hydrogenation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Such an assignment was performed semi-automatically. For instance, a standard name was automatically tagged as “catalysts” if it contained at least one of the following atoms: Zr [ 21 , 22 ], Rh, Ir, Ru, Pt, Pd, Ni, Fe, Co, Os, Cu [ 23 , 24 ], Re [ 24 ], Ag [ 23 , 25 ], Au [ 23 ], W, Mo [ 26 , 27 ], Ti [ 28 ], Mn [ 29 ], In [ 30 ]. We found that such compounds were often recorded in the Reaxys ® database in the “reagents” field.…”
Section: Computational Proceduresmentioning
confidence: 99%